Literary Production in the Quasi-Digital Society - M. Yuseano Kardiansyah; Laila Ulsi Qodriani (Journal of Language and Literature, 2025)
This article investigates the practice of literary production in the digital age, characterized by the spirit of using internet-based technological innovation, mainly social media. In this context, Indonesian literary writers often use social media platforms, especially Wattpad (a story-sharing website), to produce their literary works. Nevertheless, such a condition has not dampened the circulation of literary works in printed (conventional) form. Even though in one side they use Wattpad to publish their works, but in the other side they still follow publication system through conventional publishers. Accordingly, this particular study aims to examine the influence of technological advancement to literary production culture. Therefore, through a sociocultural approach and qualitative methods, this study is designed to observe how far the advancement of social media technology can stimulate specific behavior of literary writers in their creative process and presenting their works to the public. As a result, through exploration and analysis, it is found that social media technology could encourage digital literary production at a certain point. However, this cannot entirely make literary agents turn away from more conventional printing technology. It further reveals the strategy of literary writers with popular genre to deal with the doxa in the of Indonesian literary field. This social condition remarks the quasi-digital society.